2022
DOI: 10.1017/s1368980022000611
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum PUFA and linear growth over 12 months among 6–10 years old Ugandan children with or without HIV

Abstract: Objective: To quantify PUFA-associated improvement in linear growth among children aged 6–10 years. Design: Serum fatty acids (FA), including essential FA (EFA) (linoleic acid (LA) and α-linolenic acid (ALA)) were quantified at baseline using GC-MS technology. FA totals by class (n-3, n-6, n-9, PUFA and SFA) and FA ratios were calculated. Height-for-age Z-score (HAZ) relative to WHO population reference values were calculated longitudinally at baseline, 6 and 12 months. Linear regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 50 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…Studies that reported FA levels in child populations 16 years of age and under demonstrate that FA levels, specifically EFA levels, vary greatly (Table 1). When comparing EFA levels, child whole-blood LA levels range from a low of 8.83% total FA in Pakistan [31] to a high of 36.8% in Uganda [32,33], and child whole-blood ALA levels range from 0.17% in Pakistan [31] and 0.54% in the United Kingdom [34]. HUFA levels also demonstrated variability.…”
Section: Comparison Of Pufa Levels Between Global Child Populationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies that reported FA levels in child populations 16 years of age and under demonstrate that FA levels, specifically EFA levels, vary greatly (Table 1). When comparing EFA levels, child whole-blood LA levels range from a low of 8.83% total FA in Pakistan [31] to a high of 36.8% in Uganda [32,33], and child whole-blood ALA levels range from 0.17% in Pakistan [31] and 0.54% in the United Kingdom [34]. HUFA levels also demonstrated variability.…”
Section: Comparison Of Pufa Levels Between Global Child Populationsmentioning
confidence: 99%
“…Moreover, EPA levels varied from 0.1% in Cambodia [36] to 0.84% in Inuit children living in Canada [37], and DHA levels varied from 0.8% in Cambodian children [36] to 8.3% in South Korean children [35]. Child populations had amounts of DGLA as low as 0.56% in Uganda [32,33] and as high as 19.1 ng/uL in Gambia [38], and DTA levels as high as 3.05% in Pakistan [31] and as low as 0.018% in Uganda [32,33]. DPAn-6 levels ranged from 0.01% (in Uganda) [32,33] to 3.32 ng/uL (in Gambia) [38], while DPAn-3 levels ranged from 0.067% (in Uganda) [32,33] to 11.9 ng/uL (in Gambia) [38].…”
Section: Comparison Of Pufa Levels Between Global Child Populationsmentioning
confidence: 99%
See 3 more Smart Citations